IMPORTANCE OF THIN SEAMS RECONCILIATION IN A NEW COAL MINING PROSPECT AREA - Ali Achmad (Indonesian Mining Professionals Journal, 2021)
Coal thin seams are often considered by companies as waste material. But these seams actually can be mined potentially and giving some profit if we manage it correctly. This paper will explain about how the importance to optimize of coal thin in the mining industry with the technical and economical perspectives starting with the iso-thickness polygon in the pit shell design (sign off) to coal reserves reconciliation completely. The Geologist must undertake monthly monitoring about the sum of coal thin seams and it is variance between actual versus model. The writer takes a study case from one on the area’s PT Arutmin Indonesia concession. The location of the research area is situated in “Pit 4 Spessartine” with the coal thin seams succession from interval delta lower 2 – echo 1 lower. The Stratigraphy of the research area is a part of the Warukin Formation – Asem Asem Sub Basin. In this paper, the writer also reviewing the geological perspective so it can be known about the general parameters which controlled coal sedimentary deposited among them. We will disclose the paleo-peats distribution, paleo-base of their wetland or marsh and the last one is knowing about the water currents within the coal depositional environment.